Public Service Management Through Competence of Village Apparatus Resources in Klampok Village - Durrotul Hikmah Maulidia; Agus Suryono; ⁠Farida Nurani; Samsul Arifin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
This study examines how the competencies of village officials contribute to public service management in Klampok Village, Singosari District, Malang Regency. Despite the growing body of literature on public service and official competencies, prior studies have rarely examined these dimensions within an integrated public service management framework at the village government level, leaving a gap in understanding how competency development functions as a managerial instrument in village governance contexts. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving village officials and service users. Data analysis followed the interactive model of Miles, Huberman, and Saldãa. The findings specifically reveal that the recruitment of officials with bachelor-level education led to the proactive adoption of digital services via the village website and social media, more structured task allocation based on individual expertise, and a measurable reduction in repeat administrative visits by community members. These improvements directly strengthened the four management functions of planning, organising, actuating, and controlling public services. Competency enhancement also elevated service quality across the SERVQUAL dimensions of tangibles, reliability, responsiveness, assurance, and empathy. Nevertheless, uneven information technology skills, irregular training programs, and inadequate digital infrastructure remain persistent challenges. This study contributes theoretically by demonstrating that village officials’ competencies serve not merely as individual attributes but as integrative managerial instruments that collectively determine the effectiveness of public service management at the village level, thereby enriching the intersection of human resource competency theory and public administration in village governance.